The relationship between initial creatine phosphate breakdown and recovery oxygen consumption for a single isometric tetanus of the frog sartorius muscle at 20 degrees C (The Rockefeller University Press, 1979)
A previous paper (Mahler, M. 1978 J. Gen. Physiol. 71:559--580) describes the time-course of the suprabasal rate of oxygen consumption (delta QO2) in the sartorius muscle of R. pipiens after isometric tetani of 0.1--1.0 s at 20 degrees C. To test whether these were the responses to impulse changes in the rate of ATP hydrolysis, we compared the total suprabasal oxygen consumption during recovery (delta[O2]) with the amount of ATP hydrolyzed during a contraction, measured indirectly as the decrease in creatine phosphate (delta[CP]O). If suprabasal ATP hydrolysis during recovery is negligible in comparison with that during contraction, delta[CP]0/delta[O2] should approximate the P:O2 ratio for oxidative metabolism, which has an expected value of 6.1--6.5. We found: formula; see text. We conclude that in this muscle at 20 degrees C: (a) after a tetanus of 0.2--1.0 s, delta QO2(t) can be considered the response to an impulse increase in the rate of ATP hydrolysis; (b) the reversal during recovery of unidentified exothermic reactions occurring during the contraction (Woledge, R. C. 1971. Prog. Biophys. Mol. Biol. 22:39--74) can be coupled to an ATP hydrolysis that is at most a small fraction of delta[CP]0; (c) the pooled mean for delta[CP]0/delta[O2], 6.58 +/- 0.55, sets an experimental lower bound for the P:O2 ratio in vivo.